2012
DOI: 10.1208/s12249-012-9857-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure Relationship of Cationic Lipids on Gene Transfection Mediated by Cationic Liposomes

Abstract: Abstract. The aim of this study was to investigate the transfection efficiency of cationic liposomes formulated with phosphatidylcholine (PC) and novel synthesized diethanolamine-based cationic lipids at a molar ratio of 5:1 in comparison with Lipofectamine™ 2000. Factors affecting transfection efficiency and cell viability, including the chemical structure of the cationic lipids, such as different amine head group (diamine and polyamine; and non-spermine and spermine) and acyl chain lengths (C14, C16, and C18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
(25 reference statements)
2
21
0
1
Order By: Relevance
“…However, a decrease in transfection efficiency was observed if the weight ratio was increased above that yielding the highest transfection efficiency. This finding is in agreement with our previous reports (24,25). The highest transfection efficiency observed for the niosomes-C14, niosome-C16, and niosomes-C18 was at weight ratios of 20, 30, and 10, respectively.…”
Section: Characterization Of Cationic Niosomes and Niosomes/dna Complsupporting
confidence: 93%
“…However, a decrease in transfection efficiency was observed if the weight ratio was increased above that yielding the highest transfection efficiency. This finding is in agreement with our previous reports (24,25). The highest transfection efficiency observed for the niosomes-C14, niosome-C16, and niosomes-C18 was at weight ratios of 20, 30, and 10, respectively.…”
Section: Characterization Of Cationic Niosomes and Niosomes/dna Complsupporting
confidence: 93%
“…21,[24][25][26][27] On the other hand, we have previously shown that the use of cationic liposomes composed of EPOPC and Chol, at a 1:1 molar ratio, results in considerably higher biological activities than those obtained with other lipid-based formulations. [13][14][15][16][17]28 In this regard, the main goal of this work consisted of the development of a new gene delivery lipid-based nanosystem for HCC, targeting the ASGP-R, based on cationic liposomes composed of EPOPC, Chol and lactosyl-PE.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Among these, cationic liposome/DNA complexes (lipoplexes) have been the most extensively studied, since they present higher gene delivery efficiency, both in vitro and in vivo, than that observed with other non-viral gene delivery systems. 12,13,14 Our studies have demonstrated that cationic liposomes composed of 1-palmitoyl-2-oleoyl-snglycero-3-ethylphosphocholine (EPOPC) and cholesterol (Chol), at a molar ratio of 1:1, have the ability to mediate efficient gene delivery in different tissues and cells lines. 13,15 Lipoplexes prepared with these cationic liposomes were shown to exhibit higher levels of transfection than those obtained with nanosystems prepared with other cationic liposome formulations.…”
Section: Introductionmentioning
confidence: 99%
“…18) Recently, we described the cationic lipids 1 19) and 2 20,21) (Fig. 1) which exhibited transfection efficiency higher than and comparable to the commercially available transfection reagents.…”
Section: )mentioning
confidence: 95%